Medical consequences following endurance sports : acute pre-race illness : the effect of a screening and educational intervention program on race participation, inability to finish a race and medical complications during a race - Van Tonder, Anri (MRC/UCT RU for Exercise and Sport Medicine, 2016)
The main objectives of this dissertation was: 1) to review the available evidence with respect to the period prevalence of pre-race upper respiratory tract infections (the week before a distance running event) in distance runners, the relationship between exercise and infections, and the possible health consequences of participating in sport whilst suffering from an acute infective illness; 2) to document the period prevalence of runners with an acute illness in the 7-day period prior to an endurance race; 3) to determine the period prevalence of runners who "fail" the "neck check", and would be advised not to participate in the race, 4) to determine the incidence of runners with an acute illness, and who received educational information and guidelines, and who then not start the race, 5) to determine the incidence of runners with an acute illness who chose to start the race, but do not finish the race, and 6) to determine the incidence of runners with an acute illness who chose to start the race, but develop medical complications during the race.